Seychelles : Technical Assistance Report-Scoping the Prospects for Financial Market Development. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This Technical Assistance (TA) mission focused on scoping the prospects of developing a secondary market for government securities in Seychelles. The Central Bank of Seychelles (CBS) has a leading role in developing the financial markets and thus acted as the primary counterpart for this mission. However, due to the mission being primarily fact-finding it reached out to all various possible stakeholders; the Ministry of Finance Trade Investment and Economic Planning (MoFTIEP), commercial banks, a pension fund, insurance companies, the securities exchange, securities dealers, et cetera In addition, the mission sees the need to coordinate with the World bank (WB) and the IMF country (SYC) team as the former is providing assistance within the legal and payment system areas and the latter provides Seychelles with policy advice under the current PCI program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet